Inovasi Kemasan Ramah Lingkungan untuk Produk Gula Merah: Pelatihan Branding bagi UMKM Kampung Baduy Mualaf Lembah Barokah Ciboleger - Ignacia, Jessica Emery; Safitri, Safitri; Zunaidi, Arif; Romansyah, Nano; Safitri, Lili Dwi; Batavia, Meisya Andin; Ainina, Ananda Nur; afiyah, Anisa Nur; Putri, Fitria Dwi Risna (Fakultas Ekonomi dan Bisnis Islam, IAIN Kediri, 2025)
MSMEs in the Mualaf Baduy Village, Lembah Barokah, Ciboleger, have great potential in producing brown sugar, but still face challenges in terms of branding and marketing. One of the main obstacles is the packaging that is not attractive and not environmentally friendly, so it is less competitive in the wider market. This community service activity aims to provide training in packaging innovation using dried banana leaves as an environmentally friendly alternative to increase product appeal and strengthen MSME branding. The implementation method includes socialization of the importance of packaging, practice of making packaging based on dried banana leaves, and digital-based marketing assistance. The results of the activity showed an increase in partners' understanding of the importance of packaging in branding, as well as success in implementing new packaging that is more attractive and has high selling value. With this innovation, the brown sugar products of the Mualaf Baduy Village MSMEs are expected to be more competitive in the local and national markets.